Comparision of Mean Duration of Induction to Delivery in Isosorbide Mononitrate (Imn) plus Misoprostol between Misoprostol alone in Post-Term Pregnancies - . , Kiran; Khero, Razia Bahadur; Jhulan, Midhat Hyder; Farzana, Rukia; Karim, Kanwal; Rafique, Madiha (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare mean duration of induction to delivery in patients induced with isosorbide mononitrate (IMN) plus misoprostol versus misoprostol alone, among women with post-term pregnancies. Study Design: A Randomized Controlled Trial Place and duration: Study was conducted at department of Gynaecology and Obstetrics, Peoples University of Medical and Health Sciences for Women, Nawabshah, Sindh, from 15 May 2018 to 15 November 2018. Methodology: Total 102 pregnant women who were presented in outpatients and emergency department of hospital were recruited in this study. Study patients were divided into two equal groups by simple random method. In groups A patients IMN 40mg was used for induction of labor followed by 50 µg misoprostol and misoprostol (50 µg) alone in group B. Mean duration of induction to delivery were recorded from both groups. SPSS version 23 was used for data entry and analysis. Results: Mean age, gestational age and parity of patients were 22.9±3.7 years, 40.22±2.3 weeks and 2.9±3 respectively. Overall 39 (38.23%) patients were diabetics, 30 (58.82%) patients were anemic in our study. Mean duration of induction to delivery of group A was 32.9±3.8 hours and duration of group B was 37.2±3.6 (p-value=0.0001). Conclusion: Isosorbide mononitrate is a useful and effective medicine for artificial ripening of cervix having capability to reduce the interval of labor.